1,001 phrases you need to get a job - Schuman, Nancy; Nadler, Burton Jay, 1953- (Avon, Mass. : Adams Media, 2012)
Provides information for the job application process, providing key phrases for resumes, cover letters, and job interviews.
The winning words -- Cover letters that get noticed. Crafting your cover letter ; Writing to reach out ; Writing to respond ; Writing to engage ; Writing to inquire ; Writing for consideration -- Resumes that make a mark. Crafting your resume ; Influencing with phrases ; Adding spice ; Following up -- Interviewing phrases that close the deal. Talking the walk ; Speaking with confidence ; Speaking with authority ; Speaking with passion ; Speaking with clarity ; Speaking with skill ; Speaking with ease ; Speaking with grace ; Answering your own questions ; Describing your skills ; Writing the thank you.
Includes bibliographical references (pages 371-376) and index.
Keywords: Cover letters; Employment interviewing; Job hunting; Cover letters; Employment interviewing; Job hunting